Social Stigma as A Determinant of Tuberculosis Treatment Adherence in Public Health Centers - Retno Dewi Wulandari; Diana Tri Lestari; Muhamad Jauhar (Gaster, 2026)
Introduction: Tuberculosis (pulmonary TB) is the leading infectious disease cause morbidity and mortality in Indonesia, ranking first. This is due to poor treatment adherence related to social stigma. Pulmonary TB has physical, economic, and social impacts, while self-efficacy and social stigma contribute to treatment adherence. Objective: This study aims to analyze the relationship between social stigma and adherence to tuberculosis treatment in the productive age group. Method: The study used a descriptive correlational design with a cross-sectional approach. The independent variable was social stigma, while the dependent variable was medication adherence. The study was conducted in the Japan Community Health Center Working Area from June to August 2025 with a sample of 59 respondents using a purposive sampling technique. The research instrument was a questionnaire on social stigma and medication adherence. Data analysis used the Spearman rank test. Result: The results of the study showed that there was a statistically significant relationship between social stigma and adherence to treatment of pulmonary TB clients with a p-value of 0.000 (p < 0.05). The research results indicate a negative relationship between social stigma and adherence to pulmonary tuberculosis treatment, meaning that the higher the level of social stigma perceived by pulmonary TB patients, the lower their adherence to treatment. Conclusion: Treatment adherence is influenced by social stigma. TB patients are expected to adhere to treatment, avoid social stigma, and utilize family and community support to promote healing.